Educators’ views on human governance - Muhammad, Haslinah (2016)
Human governance has been accepted by Malaysian accounting regulatory body, yet, there is no documentation that stresses the necessity to incorporate human governance into the accounting curriculum. The objectives of this study are; (1) to provide an overview how ethics are currently embedded in accounting education curriculum by the institution, (2) to identify the current practice among accounting educators on the inclusion of ethics in the existing accounting curriculum and their recommendation for improvement and (3) to gauge accounting educators’ understanding and interpretation of the principle of human governance and consequently propose an approach of integrating human governance as a means to inculcate ethics into the curriculum. The main data sources to achieve the objectives are reviews of documents and webpages, conducts survey instrument and semi-structured interviews. Despite of an encouragement by International Education Standard (IES) 4 as well as Hala Tuju 2 and 3 in local setting, the findings show that not all accounting programmes offered by universities have a stand-alone subjects of ethics. Respondents suggest that ethics education in accounting should revisit the meaning of ethics and consider the referring to an eastern philosophy instead of the current western philosophy framework. In terms of human governance, educators view this concept as a framework of good conduct of human being which gives emphasis to both the spiritual and physical of well beings. Some perceived human governance as a “rebranded” ethics from Islamic framework. Based on the original concept of human governance, which is about externalizing the innate nature of human, human governance is applicable to all who strive to BE human. To avoid the misunderstanding and misinterpretation, human governance need to be introduce in workshop for educators in all levels. This study becomes an additional evidence regarding the need of ethics education reformation in accounting, an empirical evidence on the concept of human governance and provides implication on policy making in teaching innovation.